2023
DOI: 10.48550/arxiv.2301.01779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The James Webb Space Telescope Mission: Optical Telescope Element Design, Development, and Performance

Abstract: The James Webb Space Telescope (JWST) is a large, infrared space telescope that has recently started its science program which will enable breakthroughs in astrophysics and planetary science. Notably, JWST will provide the very first observations of the earliest luminous objects in the Universe and start a new era of exoplanet atmospheric characterization. This transformative science is enabled by a 6.6 m telescope that is passively cooled with a 5-layer sunshield. The primary mirror is comprised of 18 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Ho we ver, due to the lack of ultra-deep high-resolution imaging, and thus SL constraints far from the cluster centre, these external DM haloes were not directly constrained in these models. 1 This now changes due to the unprecedented sensitivity and spatial resolution of the JWST (Gardner et al 2006 ;McEl w ain et al 2023 ), the advent of which has already revealed numerous new SL features in several clusters and enabled significant improvements to their SL models (Caminha et al 2022 ;Hsiao et al 2022 ;Pascale et al 2022 ;Diego et al 2023 ;Mahler et al 2023 ;Meena et al 2023b ;Williams et al 2023 ). Most recently, the JWST targeted Abell 2744 in the framework of the Ultra-deep NIRSpec and NIRCam ObserVations before the Epoch of Reionization (UNCOVER) program (PIs: I. Labb é & R. Bezanson;Bezanson et al 2022 ) for wide-field ultra-deep imaging of the cluster and its surroundings (it was also observed to lesser depth in two other JWST programs; see Section 2 ).…”
mentioning
confidence: 99%
“…Ho we ver, due to the lack of ultra-deep high-resolution imaging, and thus SL constraints far from the cluster centre, these external DM haloes were not directly constrained in these models. 1 This now changes due to the unprecedented sensitivity and spatial resolution of the JWST (Gardner et al 2006 ;McEl w ain et al 2023 ), the advent of which has already revealed numerous new SL features in several clusters and enabled significant improvements to their SL models (Caminha et al 2022 ;Hsiao et al 2022 ;Pascale et al 2022 ;Diego et al 2023 ;Mahler et al 2023 ;Meena et al 2023b ;Williams et al 2023 ). Most recently, the JWST targeted Abell 2744 in the framework of the Ultra-deep NIRSpec and NIRCam ObserVations before the Epoch of Reionization (UNCOVER) program (PIs: I. Labb é & R. Bezanson;Bezanson et al 2022 ) for wide-field ultra-deep imaging of the cluster and its surroundings (it was also observed to lesser depth in two other JWST programs; see Section 2 ).…”
mentioning
confidence: 99%
“…As the accretion takes place, electromagnetic (EM) radiation is produced from tenuous hot plasma in the disk and, in most cases, from the magnetically-dominated outgoing jet launched from the poles of the BHs and its interactions with the environment (see e.g [9][10][11]). This radiation may be detectable by multiple EM instruments, such as FERMI [12], the Event Horizon Telescope [13], PanSTARRS [14], the HST [15], and JWST [16], to name just a few. Gravitational waves (GWs) from inspiralling BHBHs or even their BHdisk remnants [17,18] have been, or are expected to be, de-tected either by ground-or space-based GW observatories (see e.g.…”
Section: Introductionmentioning
confidence: 99%